The continuum of care for maternal health in Africa: A systematic review and meta-analysis. - Ritbano Ahmed; Solomon Gebre; Minychil Demelash; Tamiru Belachew; Abdurezak Mohammed; Abdulhakim Musema; Mohammed Sultan (PLoS ONE, 2024)
Background The continuum of care for maternal health (COCM) is a critical strategy for addressing preventable causes of maternal and perinatal mortality. Despite notable progress in reducing maternal and infant deaths globally, the problem persists, particularly in low-resource settings. Additionally, significant disparities in the provision of continuous care exist both between continents and within countries on the same continent. This study aimed to assess the pooled prevalence of completion across the maternity care continuum in Africa and investigate the associated factors. Methods Relevant articles were accessed through the EMBASE, CINAHL, Cochrane Library, PubMed, HINARI, and Google Scholar databases. Funnel plots and Egger's test were employed to assess publication bias, while the I-squared test was used to evaluate study heterogeneity. The inclusion criteria were limited to observational studies conducted exclusively in Africa. The quality of these studies was assessed using the JBI checklist. Data extraction from the included studies was performed using Microsoft Excel and then analysed using Stata 16 software. Results A total of 23 studies involving 74,880 mothers met the inclusion criteria. The overall prevalence of women who successfully completed the COCM was 20.9% [95% CI: 16.9-25.0]. Our analysis revealed several factors associated with this outcome, including urban residency [OR: 2.3; 95% CI: 1.6-3.2], the highest wealth index level [OR: 2.1; 95% CI: 1.4-3.0], primiparous status [OR: 1.3; 95% CI: 2.2-5.1], planned pregnancy [OR: 3.0; 95% CI: 2.3-3.7], and exposure to mass media [OR: 2.7; 95% CI: 1.9-3.8]. Conclusion The study revealed that only 20.9% of women fully completed the COCM. It also identified several factors associated with completion of the COCM, such as residing in urban areas, possessing a higher wealth index, being a first-time mother, experiencing a planned pregnancy, and having access to mass media. Based on the study's findings, it is recommended that targeted interventions be implemented in rural areas, financial assistance be provided to women with lower wealth index levels, educational campaigns be conducted through mass media, early antenatal care be promoted, and family planning services be strengthened. Review registration PROSPERO International Prospective Register of Systematic Reviews (ID: CRD42020205736).